In vitro anti-Leishmania activity of triclabendazole and its synergic effect with amphotericin B - Borges, Beatriz Santana; Bueno, Gislayne de Paula; Tomiotto-Pellissier, Fernanda; Figueiredo, Fabiano Borges; Soares Medeiros, Lia Carolina (Frontiers in Cellular and Infection Microbiology, 2023)
Introduction Leishmaniasis is a neglected tropical disease, with approximately 1 million new cases and 30,000 deaths reported every year worldwide. Given the lack of adequate medication for treating leishmaniasis, drug repositioning is essential to save time and money when searching for new therapeutic approaches. This is particularly important given leishmaniasis’s status as a neglected disease. Available treatments are still far from being fully effective for treating the different clinical forms of the disease. They are also administered parenterally, making it challenging to ensure complete treatment, and they are extremely toxic, in some cases, causing death. Triclabendazole (TCBZ) is a benzimidazole used to treat fasciolosis in adults and children. It presents a lower toxicity profile than amphotericin B (AmpB) and is administered orally, making it an attractive candidate for treating other parasitoses. The mechanism of action for TCBZ is not yet well understood, although microtubules or polyamines could potentially act as a pharmacological target. TCBZ has already shown antiproliferative activity against T. cruzi, T. brucei, and L. infantum. However, further investigations are still necessary to elucidate the mechanisms of action of TCBZ. Methods Cytotoxicity assay was performed by MTT assay. Cell inhibition (CI) values were obtained according to the equation CI = (O.D treatment x 100/O.D. negative control). For Infection evaluation, fixated cells were stained with Hoechst and read at Operetta High Content Imaging System (Perkin Elmer). For growth curves, cell culture absorbance was measured daily at 600 nm. For the synergism effect, Fractional Inhibitory Concentrations (FICs) were calculated for the IC50 of the drugs alone or combined. Mitochondrial membrane potential (DYm), cell cycle, and cell death analysis were evaluated by flow cytometry. Reactive oxygen species (ROS) and lipid quantification were also determined by fluorimetry. Treated parasites morphology and ultrastructure were analyzed by electron microscopy. Results The selectivity index (SI = CC50/IC50) of TCBZ was comparable with AmpB in promastigotes and amastigotes of Leishmania amazonensis. Evaluation of the cell cycle showed an increase of up to 13% of cells concentrated in S and G2, and morphological analysis with scanning electron microscopy showed a high frequency of dividing cells. The ultrastructural analysis demonstrated large cytoplasmic lipid accumulation, which could suggest alterations in lipid metabolism. Combined administration of TCBZ and AmpB demonstrated a synergistic effect in vitro against intracellular amastigote forms with cSFICs of 0.25. Conclusions Considering that TCBZ has the advantage of being inexpensive and administrated orally, our results suggest that TCBZ, combined with AmpB, is a promising candidate for treating leishmaniasis with reduced toxicity.